Burn scar contracture release surgery effectively improves functional range of motion, disability and quality of life: A pre/post cohort study with long-term follow-up in a Low- and Middle-Income Country. Issue 6 (September 2021) - Hendriks, T.C.C.; Botman, M.; de Haas, L.E.M.; Mtui, G.S.; Nuwass, E.Q.; Jaspers, M.E.H.; Niemeijer, A.S.; Nieuwenhuis, M.K.; Winters, H.A.H.; van Zuijlen, P.P.M.
Highlights: This is the first study globally that evaluated the functional impact of contracture release surgery. Contracture release surgery effectively improves joint function, reduces disability, and improves QoL. Regaining a functional joint after surgery is associated with less disability and higher QoL. Future studies that evaluate joint flexibility problems should assess functional ROM, disability and QoL. Abstract: Objective: Burn scar contractures limit range of motion (ROM) of joints and have substantial impact on disability and the quality of life (QoL) of patients, particularly in a Low- and Middle-Income Country (LMIC) setting. Studies on the long-term outcome are lacking globally; this study describes the long-term impact of contracture release surgery performed in an LMIC. Methods: This is a pre-post cohort study, conducted in a referral hospital in Tanzania. Patients who underwent burn scar contracture release surgery in 2017–2018 were eligible. ROM (goniometry), disability (WHODAS 2.0) and QoL (EQ-5D) were assessed. The ROM data were compared to the ROM that is required to perform activities of daily living without compensation, i.e. functional ROM. Assessments were performed preoperatively and at 1, 3, 6 and 12 months postoperatively. Results: In total, 44 patients underwent surgery on 115 affected joints. At 12 months, the follow-up rate was 86%. The mean preoperative ROM was 37.3% of functional ROM (SD 31.2). This improved up to 108.7% at 12 months postoperatively (SD 42.0, p < 0.001). Disability-free survival improved from 55% preoperatively to 97% at 12 months ( p < 0.001) postoperatively. QoL improved from 0.69 preoperatively, to 0.93 (max 1.0) at 12 months postoperatively ( p < 0.001). Patients who regained functional ROM in all affected joints reported significantly less disability ( p < 0.001) and higher QoL ( p < 0.001) compared to patients without functional ROM. Conclusions: Contracture release surgery performed in an LMIC significantly improved functional ROM, disability and QoL. Results showed that regaining a functional joint is associated with less disability and higher QoL.